Low complexity decoder over time-selective fading channels - ZHANG Bi-jun; ZHU Guang-xi; SUN Jun; LIU Wen-ming (Tongxin xuebao)
A low complexity decoder was presented applicable to time-selective fading channels based on the existed group layered space-time （GLST） architecture. The intra symbol interferences within the all groups were firstly sup-pressed in virtue of the construction of orthogonal matrices and then obtained the all groups’ transmitted symbols based on the group detection technique using the simplified matrix inverse algorithm. The computational complexities of the proposed decoder were decreased greatly compared with the existed conversational decoding scheme. The simulation re-sults also show that the two kinds of decoders obtain the almost same performance at the minimum receiver antenna number under various time variations of channels and group number. At the same time, the performances of the two kinds of decoders get worse as the increase of time variations of channels or the group number but the performance loss can be compensated by the increase of receive antenna number.